Impact of transcatheter mitral valve edge‐to‐edge repair on atrial fibrillation burden: Insights from a multicenter cohort. Issue 2 (20th December 2022) - Trankle, Cory R.; Rodriguez Lozano, Patricia F.; Mahoney, Paul D.; Haughey, Sean; May, Jennifer F.; Rombaoa, Patricia; Miller, Lauren; Lim, Scott; Gertz, Zachary M.
Abstract: Background: Patients with significant mitralregurgitation (MR) often experience atrial fibrillation (AF). The effects of transcatheter edge‐to‐edge repair (TEER) for MR on AF burden is unknown. Methods: Patients who underwent TEER atthree institutions who also had a cardiac implantable electronic device with aright atrial lead were retrospectively identified. In patients with baseline AF, device data onAF burden and echocardiographic changes were recorded at baseline and 3‐ and 12‐month follow up time points when available. Data is expressed as number (%) and median (interquartile range), withpaired values analyzed using the Wilcoxon signed‐rank test. Results: Overall 66 patients wereidentified, of whom 54 (82%) had baseline data on AF available for review. Of these, 18 (33%) had a baseline burden ofAF (median burden 100% [54–100%]). Patients were 77 (71–83) years old, 10 (56%) male, 14 (78%) White, and 3 (17%) Black. A significant reduction in AF burdenwas observed at 3 months (11 patients, p = 0.03) which did not retainsignificance at 12 months (8 patients, p = 0.69). Indexed maximal left atrial volumes did not significantly change inthose with paired studies available ( p > 0.35 for both time points). Conclusions: In this multicenter cohort, one thirdof patients with severe MR undergoing TEER had an AF burden at baseline, whichwas found to be significantly lower at 3 month follow up. Further investigation is needed to confirm thefindings of this small cohort and determine its effects on downstream sequelaeof AF.